PHARMACOVIGILANCE IN HEMOTHERAPY: MONITORING TRANSFUSION REACTIONS AND PATIENT SAFETY (CIPEEX, 2025)
Pharmacovigilance and haemovigilance are complementary and fundamental areas for ensuringtransfusion safety in hemotherapy. This simple abstract addresses the concepts, classification oftransfusion reactions, protocols for reporting and investigation, the role of the clinical pharmacist,electronic monitoring systems, epidemiological data in Brazil, current challenges, and the guidelinesof ANVISA and the Brazilian Society of Hematology and Hemotherapy (SBHH). The researchincludes normative analysis, review of technical-scientific literature, assessment of recent nationalepidemiological data, and examination of monitoring systems and emerging technologies. Theregulatory advances of RDC nº 34/2014 and IN nº 196/2022 are highlighted, as are multidisciplinaryapproaches, the use of the Notivisa system, the evolution of compliance indicators, challenges relatedto underreporting and professional qualification, and international trends such as AI integration inpharmacovigilance processes. These strategies underpin the continuous improvement of patient safety,process quality, and national institutional effectiveness
Keywords: Hemovigilance; Pharmacovigilance; Transfusion Reactions; Patient Safety; Hemotherapy